The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/aps.2009.156
|View full text |Cite
|
Sign up to set email alerts
|

β-Naphthoflavone protects mice from aristolochic acid-I-induced acute kidney injury in a CYP1A dependent mechanism

Abstract: Aim:The role of CYP1A in the protection of aristolochic acid (AA)I-induced nephrotoxicity has been suggested. In the present study we investigated the effects of β-naphthoflavone (BNF), a non-carcinogen CYP1A inducer, on AAI-induced kidney injury. Methods: Mice were pretreated with 80 mg/kg BNF by daily intraperitoneal injection (ip) for 3 days followed by a single ip of 10 mg/kg AAI. AAI and its major metabolites in blood, liver and kidney, the expression of CYP1A1 and CYP1A2 in microsomes of liver and kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…Consistent with this report, AAIa was not detected in renal microsomes (data not shown). Induction of CYP1A activity with 3-MC or ␤-naphthoflavone (Xiao et al, 2009) increases resistance to AAI-elicited nephrotoxicity. In this study, 3-MC treatment increased hepatic microsomal AAI demethylation activity in both control and CYP1A2-null mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this report, AAIa was not detected in renal microsomes (data not shown). Induction of CYP1A activity with 3-MC or ␤-naphthoflavone (Xiao et al, 2009) increases resistance to AAI-elicited nephrotoxicity. In this study, 3-MC treatment increased hepatic microsomal AAI demethylation activity in both control and CYP1A2-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, pretreatment of mice with 3-methylcholanthrene or ␤-naphthoflavone (Xiao et al, 2009), agonists of the arylhydrocarbon receptor that induce CYP1 enzymes and other xenometabolizing activities, protects mice from AA.…”
mentioning
confidence: 99%
“…1) For safe clinical use, it is quite necessary to evaluate the toxicity of AF and HAF since relatively high contents of AAs are found in them. Up to now, the pharmacological and toxicological actions of AAs, [4][5][6][16][17][18][19][20] A. manshuriensis [21][22][23] and A. fangchi [24][25][26] were well known, but only one piece of literature could be accessed on the subchronic toxicity of the aqueous extract of AF. 27) Drug processing is a traditional pharmaceutical technology in China, and plays an important role in reducing the toxicity of the traditional drugs.…”
Section: Acute and Subacute Toxicity Of The Extract Of Aristolochiae mentioning
confidence: 99%
“…Previous studies have indicated that α-Napthoflavone inhibits OS and serves potential roles is estrogen-induced breast carcinogenesis and ultraviolet-led human skin aging (27,28). β-Naphthoflavone has been demonstrated to protect mice against aristolochic acid-I-induced acute kidney injury, and to attenuate hyperoxic lung injury in premature infants primarily via mitigating OS (29,30). In the present study, α-and β-Naphthoflavone were identified to effectively antagonize the apoptosis-promoting effect of H 2 O 2 on neuronal SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%